2013
DOI: 10.1175/mwr-d-12-00123.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Cold Core Eddy on Tropical Cyclone Intensity and Structure under Idealized Air–Sea Interaction Conditions

Abstract: The impacts of ocean feedback on tropical cyclones (TCs) are investigated using a coupled atmosphereocean model under idealized TC and cold core eddy (CCE) conditions. Results reveal negative impacts of the ocean coupling on TC development. The cold wake induced by a TC not only weakens the TC intensity but also limits the expansion of the storm circulation. The presence of CCE has boosted the TC-induced sea surface temperature cooling, which conversely inhibits the TC development. The TC appears to be weakene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
38
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 55 publications
(75 reference statements)
0
38
0
Order By: Relevance
“…Note that there are some important differences among these schemes, including the handling of the turbulent Prandtl number, diffusion above the boundary layer, and specification of the critical bulk‐Richardson number (Bu et al, ). Although the K‐profile parameterization scheme has its limitations as cautioned by Kepert (), it has been proved to work well in modeling the intensity and structure of tropical cyclones (e.g., Ma et al, ; Ma, Fei, Huang, et al, ; Ma, Fei, Cheng, et al, ; Nolan, Zhang, et al, ; Nolan, Stern, et al, ; Zhang et al, ), and performs satisfactorily in the HWRF model (Gopalakrishnan et al, ; Zhang et al, , ). As a typical K‐profile parameterization scheme, the YSU scheme is chosen to parameterize boundary‐layer processes in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Note that there are some important differences among these schemes, including the handling of the turbulent Prandtl number, diffusion above the boundary layer, and specification of the critical bulk‐Richardson number (Bu et al, ). Although the K‐profile parameterization scheme has its limitations as cautioned by Kepert (), it has been proved to work well in modeling the intensity and structure of tropical cyclones (e.g., Ma et al, ; Ma, Fei, Huang, et al, ; Ma, Fei, Cheng, et al, ; Nolan, Zhang, et al, ; Nolan, Stern, et al, ; Zhang et al, ), and performs satisfactorily in the HWRF model (Gopalakrishnan et al, ; Zhang et al, , ). As a typical K‐profile parameterization scheme, the YSU scheme is chosen to parameterize boundary‐layer processes in this study.…”
Section: Introductionmentioning
confidence: 99%
“…With this aim, the air‐sea coupling numerical simulations by Ma et al . [] are used, but with the time intervals of model output improved from 1 h to 10 min. Section 2 describes briefly the model setup.…”
Section: Introductionmentioning
confidence: 99%
“…By analyzing four typical tropical cyclones in the South China Sea, Zhang et al concluded that the stronger the intensity of a tropical cyclones, the slower the movement speed, the shallower the mixed layer depth, and the greater the reduction in SST [24]. On the other hand, pre-existing cold eddies would enhance the SSC caused by the typhoons [8,26,27], whereas the SST drop in a warm-eddy-controlled region might not be very obvious [24,25].…”
Section: Introductionmentioning
confidence: 99%